2011
DOI: 10.1371/journal.pone.0021412
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Characterization of an AT-Hook Protein from Leishmania

Abstract: AT-rich DNA, and the proteins that bind it (AT-hook proteins), modulate chromosome structure and function in most eukaryotes. Unlike other trypanosomatids, the genome of Leishmania species is unusually GC-rich, and the regulation of Leishmania chromosome structure, replication, partitioning is not fully understood. Because AT-hook proteins modulate these functions in other eukaryotes, we examined whether AT-hook proteins are encoded in the Leishmania genome, to test their potential functions. Several Leishmani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Studies from several groups, including ours, indicated that EBNA1's AT-hooks were essential to recruit ORC to DS (Sears, Ujihara et al 2004;Norseen, Thomae et al 2008). This conclusion has been reiterated by our observations that chimeric proteins in which ATH1 and ATH2 were substituted by cellular AT-hook proteins support licensed replication from DS (Sears, Kolman et al 2003;Kelly, Singh et al 2011). Lieberman and co-workers have demonstrated that EBNA1 uses its AT-hooks to recruit the ORC complex to DS via a Gquadruplex RNA intermediate, underscoring a critical role for these domains in oriPreplication (Norseen, Thomae et al 2008).…”
Section: Contributions Of Ebna1 To the Licensed Replication And Segrementioning
confidence: 76%
See 1 more Smart Citation
“…Studies from several groups, including ours, indicated that EBNA1's AT-hooks were essential to recruit ORC to DS (Sears, Ujihara et al 2004;Norseen, Thomae et al 2008). This conclusion has been reiterated by our observations that chimeric proteins in which ATH1 and ATH2 were substituted by cellular AT-hook proteins support licensed replication from DS (Sears, Kolman et al 2003;Kelly, Singh et al 2011). Lieberman and co-workers have demonstrated that EBNA1 uses its AT-hooks to recruit the ORC complex to DS via a Gquadruplex RNA intermediate, underscoring a critical role for these domains in oriPreplication (Norseen, Thomae et al 2008).…”
Section: Contributions Of Ebna1 To the Licensed Replication And Segrementioning
confidence: 76%
“…EBNA1 mutants in which either ATH1 or ATH2 is deleted retain the capacity to bind mitotic chromosomes and support the segregation of oriP-plasmids (Sears, Ujihara et al 2004). Further, both ATH1 and ATH2 can be substituted by cellular AT-hook proteins, and the resulting chimeras associate with mitotic chromosomes and support segregation of oriP-plasmids (Hung, Kang et al 2001;Sears, Kolman et al 2003;Kelly, Singh et al 2011). Because both ATH1 and ATH2 function equivalently to support oriP-plasmid segregation, but only ATH2 associates with EBP2/p40, it is likely that EBP2 does not mediate the partitioning of oriP-plasmids or EBV genomes.…”
mentioning
confidence: 99%
“…The multi-subunit ORC complex in budding and fission yeast recognizes AT-rich DNA sequences (Chuang & Kelly, 1999;Kelly et al, 2011) (Table 1). AT-rich sequences have been associated with DNA replication, repair and transcription in many eukaryotes and are recognized by AT-hook motifs.…”
Section: Initiation Of Dna Replication and Prevention Of Rereplicationmentioning
confidence: 99%
“…These motifs can bind to the minor groove of AT-rich DNA, thus inducing a conformational change or recruiting other proteins (Kelly et al, 2011). In fission yeast, the Orc4 subunit contains nine AT-hooks, whereas S. cerevisiae Orc2 contains only one AT-hook (Chuang & Kelly, 1999;Kelly et al, 2011). HMGA1a is a classic AT-hook protein.…”
Section: Initiation Of Dna Replication and Prevention Of Rereplicationmentioning
confidence: 99%
See 1 more Smart Citation